Pengembangan Bahan Ajar Berbasis E-Modul Mata Kuliah Komunikasi Perkantoran Pada Mahasiswa S1 Pendidikan Administrasi Perkantoran Di Unesa - Risky Octa Vianis; Siti Sri Wulandari; Finisica Dwijayanti Patrikha (Universitas Negeri Surabaya, 2021)
This development research aims to determine the development process, feasibility, and student responses to module-based teaching materials in the office communication course in the UNESA Office Administration Education undergraduate study program. The data analysis technique used is quantitative descriptive analysis. The results of the study stated that the development of e-module-based teaching materials was carried out according to the 4D development model which only reached the development stage. The results of expert validation and the results of a limited trial of e-module-based teaching materials for students are categorized as very feasible. This shows that the e-module-based teaching materials that have been developed by researchers are declared very suitable for use in learning.